2011
DOI: 10.1177/1553350611409063
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Surgical Innovations

Abstract: SLNB is a complex innovation to adopt. Successful adoption was assisted by a high-volume breast cancer surgical champion, interprofessional communication, and administrative support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In some cases, the implementation of TAVI resulted in a better collaboration between both departments. The interviews indicate that this depended on central actors, which underscores previous research [ 22 ]. Champions, eager to implement the method, facilitated the dialogue between both departments and took initiative to drive the process forward.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In some cases, the implementation of TAVI resulted in a better collaboration between both departments. The interviews indicate that this depended on central actors, which underscores previous research [ 22 ]. Champions, eager to implement the method, facilitated the dialogue between both departments and took initiative to drive the process forward.…”
Section: Discussionsupporting
confidence: 76%
“…Several theories and models can be applied to better understand the implementation and diffusion of innovations in healthcare—most notably, Everett M. Rogers’ Diffusion of Innovations (DOI) theory [ 19 ], as well as the diffusion of innovations model described by Greenhalgh et al [ 20 ]. Both have been adopted in numerous studies analyzing the implementation and diffusion of innovations in healthcare (see, for example, [ 1 , 21 , 22 ]). Roger’s DOI theory has been picked up by multiple researchers in various contexts and disciplines to explain the spread of emerging innovations.…”
Section: Introductionmentioning
confidence: 99%
“…This result was mirrored by Anderson et al; studying the adoption of minimally invasive prostatectomy during the early 2000s, they commented that surgeons were more likely to adopt and continue novel surgical practices if working with other urologists and trained in those techniques. From a systems perspective, Wright et al (2011) reported that the adoption of sentinel lymph node biopsy for breast cancer was more avid where high-volume surgeons actively championed the technique, while hospital administrators were more likely to accept variation in practice when presented with guidelines statements to support the change [25]. Perhaps the adoption of supine RALP will lag until a critical mass of surgeons vocally supports or advocates for it to the broader urologic community.…”
Section: Discussionmentioning
confidence: 99%
“…[911] Before SLNB was introduced, the more invasive axillary lymph node dissection (ALND) was the standard of care. [9, 12, 13] Research demonstrated that SLNB is associated with similar survival benefit to ALND, yet has much less morbidity. Several health system factors have been associated with increased probability of a woman having SLNB, while at the same time there is evidence of disparities within some populations.…”
Section: Introductionmentioning
confidence: 99%